A few comments on a result of A. Novikov and Girsanov's theorem. Issue 8 (17th November 2019) - Krylov, N. V.
ABSTRACT: We give a simple proof that for a continuous local martingale M t lim _ ε ↓ 0 ⁡ ε log ⁡ E e ( 1 − ε ) ⟨ M ⟩ ∞ / 2 < ∞ ⟹ E exp ⁡ ( M ∞ − ⟨ M ⟩ ∞ / 2 ) = 1.